2019
DOI: 10.1139/cjz-2018-0247
|View full text |Cite
|
Sign up to set email alerts
|

Tree Swallow (Tachycineta bicolor) nest success and nestling growth near oil sands mining operations in northeastern Alberta, Canada

Abstract: Industrial development and contaminant exposure may affect reproductive success and food quality for birds. Tree Swallows (Tachycineta bicolor (Vieillot, 1808)) nesting near oil sands development in northern Alberta (Canada) potentially experience elevated environmental stressors that could influence reproduction. We measured reproductive and growth endpoints in Tree Swallows, predicting reduced reproductive success and nestling growth near oil sands operations compared with reference sites. We also identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 74 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…Dickcissel abundance decreased with increased precipitation during the breeding season but not the non-breeding season (when they are away), implying that negative effects of increased precipitation on dickcissels stem from direct effects during the breeding season, such as emigration due to heavy precipitation and related extreme events including flooding and summer hailstorms. High precipitation and extreme precipitation events may also cause direct mortality of adults and nestlings as well as nest failures, and changes in precipitation may influence exposure to predators (e.g., Takagi, 2001;Mattsson and Cooper, 2009;Robinson et al, 2017;Godwin et al, 2019). Dickcissels showed high site fidelity, with 70-93% of recaptures occurring at the same site as that of initial capture.…”
Section: Discussion Dickcissel Relationships With Precipitation and Grassland Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Dickcissel abundance decreased with increased precipitation during the breeding season but not the non-breeding season (when they are away), implying that negative effects of increased precipitation on dickcissels stem from direct effects during the breeding season, such as emigration due to heavy precipitation and related extreme events including flooding and summer hailstorms. High precipitation and extreme precipitation events may also cause direct mortality of adults and nestlings as well as nest failures, and changes in precipitation may influence exposure to predators (e.g., Takagi, 2001;Mattsson and Cooper, 2009;Robinson et al, 2017;Godwin et al, 2019). Dickcissels showed high site fidelity, with 70-93% of recaptures occurring at the same site as that of initial capture.…”
Section: Discussion Dickcissel Relationships With Precipitation and Grassland Managementmentioning
confidence: 99%
“…In other riparian ecosystems, higher avian productivity has also been found to be positively correlated with precipitation, such as in Louisiana waterthrush (Parkesia motacilla; Mattsson and Cooper, 2009) and Mississippi kites (Ictinia mississippiensis; Welch-Acosta et al, 2019). By contrast, in other ecosystems, higher precipitation resulted in higher losses of nestlings to predators in bull-headed shrikes (Lanius bucephalus) (Takagi, 2001) and lower productivity in peregrine falcons (Falco peregrinus; Robinson et al, 2017) and tree swallows (Tachycineta bicolor; Godwin et al, 2019).…”
Section: Dickcissel and Cowbird Productivity And Implications For Population Trendsmentioning
confidence: 99%
“…For example, the strength of bacula in river otters (Lontra canadensis) was statistically lower than greater concentrations of some petrogenic compounds in liver tissue, but in some cases the inverse effect was also observed (Thomas et al, 2021), which highlights the complexity of such relationships and the challenges associated with working with limited sample sizes in complex environments. Although the spatial trends are consistent, it should be noted that causal relationships have not been demonstrated in these studies, and other contaminant-related work has identified other important natural covariates contributing to observed responses (Godwin et al, 2019;Hebert, 2019;Tetreault et al, 2020). However, preliminary analyses in the water review suggest some influence of industrial activity in fish captured in the high deposition zone (Arciszewski et al, forthcoming).…”
Section: Contaminantsmentioning
confidence: 61%
“…Dickcissel abundance decreased with increased precipitation during the breeding season but not the non-breeding season (when they are away), implying that negative effects of increased precipitation on dickcissels stem from direct effects during the breeding season, such as emigration due to heavy precipitation and related extreme events including flooding and summer hailstorms. High precipitation and extreme precipitation events may also cause direct mortality of adults and nestlings as well as nest failures, and changes in precipitation may influence exposure to predators (e.g., Takagi, 2001;Mattsson and Cooper, 2009;Godwin et al, 2019). Dickcissels showed high site fidelity, with 70-93% of recaptures occurring at the same site as that of initial capture.…”
Section: Discussion Dickcissel Relationships With Precipitation and Grassland Managementmentioning
confidence: 99%